Anandamide modulation of monocyte-derived Langerhans cells: implications for immune homeostasis and skin inflammation - Pénzes, Zsófia; Horváth, Dorottya; Molnár, Petra; Fekete, Tünde; Pázmándi, Kitti; Bácsi, Attila; Szöllősi, Attila Gábor (Frontiers in Immunology, 2024)
Introduction: The endocannabinoid system (ECS), the cannabis plant, is a regulatory network that plays crucial roles in skin health and disease. Endogenous ligands of the ECS, endocannabinoids, are important regulators of immune responses. Arachidonoylethanolamide (known as anandamide), is known for its anti-inflammatory effects. Langerhans cells (LCs) are the sole antigen-presenting cells present in the human epidermis. Little is known about the effect of endocannabinoids on these cells. Our research aimed to provide the connection between monocyte-derived Langerhans cells (moLCs) and the ECS. Methods: Human monocytes were differentiated into moLCs using established protocols. Anandamide was applied during the differentiation process to test its effect on the viability, marker expression, and cytokine production of the cells, as well as in short term treatments for intracellular calcium measurement. TLR ligands applied after the differentiation protocol were used to activate moLCs. The impact of anandamide on the functionality of moLCs was further assessed using differential gene expression analysis of bulk RNA-Seq data, moLC-T cell cocultures, while ELISpot was employed to determine polarization of T cells activated in the aforementioned cocultures. Results: Anandamide did not significantly affect the viability of moLCs up to 10 µM. When applied during the differentiation process it had only a negligible effect on CD207 expression, the prototypic marker of LCs; however, there was an observed reduction in CD1a expression. Anandamide had no significant effects on the maturation status of moLCs, nor did it affect the maturation induced by TLR3 and TLR7/8 agonists. MoLCs differentiated in the presence of anandamide did however show decreased production of CXCL8, IL-6, IL-10 and IL-12 cytokines induced by TLR3 and TLR7/8 activation. Anandamide-treated moLCs showed an increased capability to activate naïve T cells; however, not to the level seen with combined TLR agonism. RNA sequencing analysis of moLCs differentiated with anandamide showed modest changes compared to control cells but did reveal an inhibitory effect on oxidative phosphorylation specifically in activated moLCs. Anandamide also promoted the polarization of naïve T cells towards a Th1 phenotype. Discussion: Our results show that anandamide has nuanced effects on the differentiation, maturation, cytokine secretion, metabolism and function of activated moLCs.